A 10-year Retrospective Study of Primary Hyperparathyroidism in Children - Li, C.-C.; Yang, C.; Wang, S.; Zhang, J.; Kong, X.-R.; Ouyang, J. (Experimental and Clinical Endocrinology & Diabetes, 2012)
Primary hyperparathyroidism (PHPT) in children is thought to be extremely rare. The exact incidence is unknown and little is known of the characteristics of the disease. We reviewed our experience with PHPT to better characterize these patients.We carried out a retrospective study in 12 patients (age 9–16 years) who had surgical treatment between 2001 and 2011 in a single institution.There were 5 male subjects and 7 female subjects. The diagnosis of PHPT in pediatric patients is frequently delayed with an average time of 41 months. The main signs of PHPT were urinary and bone disorders, as well as non-specific signs. All patients had preoperative localization studies prior to operation. Combined using of neck sonography, MIBI-scintigraphy and CT and/or MRI, our patients had a positive predictive value of 100%. After operation, all patients were confirmed to have parathyroid adenoma. 1 patient had 2 adenomas, 1 of which was an ectopic adenoma located in the mediastinum. 9 patients experienced symptomatic hypocalcemia postoperatively. No patients had any serious long-term effects from parathyroidectomy at our institution. All patients were cured after removal of the parathyroid adenoma. No permanent complication was observed for all patients.PHPT in children is rare, the commonest signs are urinary and bone tissue impairment, as well as non-specific signs. Evaluation of serum calcium and PTH levels is diagnostic in suspected patients. Preoperative localization is essential. Surgery is without significant complications. Surgical treatment of PHPT is curative and definitive.
Keywords: primary hyperparathyroidism; pediatrics; calcium supplementation; parathyroid hormone